Farmer- Herder Conflicts and the Socio-Economic Predicaments of Women in North Central Nigeria - Gbamwuan, Asor; Atim, Grace (Advances in Social Sciences Research Journal, 2022)
Farmer-Herder conflicts in North Central Nigeria have been rife since 1999. The emergence, development, and intensity of these clashes are underpinned by socio-economic, religious, and political undertones. Majorly, the area is endowed with fertile land, abundant water, and mineral resources attracting peasant farmers and herders for sustenance. The study made use of both primary and secondary sources. The study discovers that women are a powerful force in agricultural production, processing, and utilisation, and were seriously affected by these conflicts. This is because women have been killed, displaced, raped, and maimed, while their farming activities were truncated leading to joblessness, abject poverty, and food insecurity. Against this background, the study suggests that the government and other humanitarian bodies should focus on women empowerment programmes in North Central Nigeria. While anti-open grazing laws should be enforced in a manner to ensure that both farmers and herders live a symbiotic, resourceful, peaceful, and harmonious life in Central Nigeria.